The toxicity of ochratoxin to ruminants. - Ribelin, W E (1978)
Among the mold toxins the most toxic ochratoxin, ochratoxin A, commonly occurs in many grains, other feedstuffs, and in soil but in low concentrations. The amount required to produce acute toxicity in ruminants makes such occurrences unlikely. Toxic effects are more likely to occur in chronic low-level intoxication. The lethal single oral dose in cattle is high, probably being a few milligrams more than 13 mg/kg. The lethal level produced by repeated feeding to goats was 3 mg/kg. Ochratoxin A occurred in cows milk and urine but only when massive doses were ingested. Abortion or fetal death, though occurring in rodents, are unlikely to be induced in cattle.